2018
DOI: 10.1007/s00348-018-2598-9
|View full text |Cite
|
Sign up to set email alerts
|

Upstream shear-layer stabilisation via self-oscillating trailing edge flaplets

Abstract: This is the published version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThe flow around a symmetric aerofoil (NACA 0012) with an array of flexible flaplets attached to the trailing edge has been investigated at Reynolds numbers of 100,000-150,000 using high-speed time-resolved particle image velocimetry (HS TR-PIV) and motion tracking of the flaplets' tips. Particular attention has been made on the upstream effect on the boundar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
(46 reference statements)
2
12
0
Order By: Relevance
“…Furthermore, Talboys et al (2019) indicated that the tonal noise can be removed when the passive flaplets are affixed to the pressure side of the airfoil, whereas the tonal noise can be attenuated if the flaplets are placed on the suction side of the airfoil. Talboys et al (2018) also analyzed different motions of the trailing edge flaplet and found that the movement of the trailing edge is primarily due to small scale turbulent structures, and therefore, the flaplets are able to stabilize the shear layer on the suction side to promote the performance of the airfoil. Our experimental investigation showed that the real fringe feather edges installed on an airfoil enables the large-scale vortex to break down into small-scale turbulence (Yang et al, 2015), demonstrating that the vibrating long flexible fringe contributes an important vertical velocity in the flow field around the trailing edge.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Talboys et al (2019) indicated that the tonal noise can be removed when the passive flaplets are affixed to the pressure side of the airfoil, whereas the tonal noise can be attenuated if the flaplets are placed on the suction side of the airfoil. Talboys et al (2018) also analyzed different motions of the trailing edge flaplet and found that the movement of the trailing edge is primarily due to small scale turbulent structures, and therefore, the flaplets are able to stabilize the shear layer on the suction side to promote the performance of the airfoil. Our experimental investigation showed that the real fringe feather edges installed on an airfoil enables the large-scale vortex to break down into small-scale turbulence (Yang et al, 2015), demonstrating that the vibrating long flexible fringe contributes an important vertical velocity in the flow field around the trailing edge.…”
Section: Introductionmentioning
confidence: 99%
“…The Eigen frequency of the flaplets needs to be determined in order to see at what frequency the flaplets will oscillate in the flow. The set-up and image processing for this response test is the same as was used in [21]. The normalised response of the long, baseline and short flaplets is shown in Fig.…”
Section: Static Flaplet Responsementioning
confidence: 99%
“…However the authors have two concepts of thought on the source of the reduction. The first is the hypothesis of the lock-in effect documented in [21] (flaplets act as pacemaker), which plays an important role in the stabilisation of the T-S waves. Because of the different Eigen frequencies of the flaplets, they are modifying the wake with different frequencies, hence the different acoustic frequency reductions.…”
Section: Variation In Flaplet Lengthmentioning
confidence: 99%
See 2 more Smart Citations